LITHIUM SPOTS IN THE NORTHERN roAP STAR HD 12098 - Shavrina, A. V.; Glagolevskij, Yu. V.; Drake, N. A.; Polosukhina, N. S.; Pavlenko, Ya. V.; Kudryavtsev, D. O. (Одеські астрономічні публікації, 2008)
—